The production of homozygous diploid lines by means of the haploid technique in South African barley cultivars - Littlejohn, Gail M.(Gail Margaret) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1986.